2020
DOI: 10.3390/su12062569
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning Communities for Sustainable Employment through Visual Tools

Abstract: Higher education institutions must enable students to acquire skills and capacities that prepare them for working life and enhance their employability. This will lead to an applied learning- and teaching-enhancement-oriented sustainable Higher Education System. This research aims to contribute to that goal by analyzing student interactions in a collaborative learning community. It assesses the impact of visual tools on academic performance and student satisfaction in employment-focused blended studies, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…Indeed, educational practices have been transformed by digital media into active methodologies that allow the student to have an active role in the learning processes, interacting with peers and technologies over time [13,14]. In particular, social online networking communities can be considered a public space for socialization, interaction, creation, and diffusion of culture and identity; a place where people can participate, learn, and bring about social transformation [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, educational practices have been transformed by digital media into active methodologies that allow the student to have an active role in the learning processes, interacting with peers and technologies over time [13,14]. In particular, social online networking communities can be considered a public space for socialization, interaction, creation, and diffusion of culture and identity; a place where people can participate, learn, and bring about social transformation [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are consistent with a randomized controlled trial conducted in Brazil that involved 60 pregnant women with lumbopelvic pain. This trial found that the hatha yoga exercise was effective in reducing pain after 10 time-practice (Martín-García et al, 2020). In addition, a prospective randomized controlled pilot clinical trial involving 115 pregnant women without complications in Israel showed that yoga was safe for pregnant women without any adverse effects and it was able to improve biomechanics (gait speed, turn time, double support time and instrumented timed-up and go), so that it has the effect of reducing bodily discomfort due to pelvic pain (Holden et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…This was because in this game there had been many messages in the form of writing, letters, pictures, and symbols that encouraged participants to involve more than one of their five senses to interpret them (Nachiappan, 2017;Prayuni et al, 2018). In other study, the simulation method with the game of snakes and ladders had been shown to be able to make a passive learning atmosphere become active which allowed them to capture more information effectively and efficiently though the had been discussing difficult things (Annamalai et al, 2015;Martín-García et al, 2020;Nachiappan, 2017). The success of learning by including play activities could not be separated from the conceptual impact of the method as explained by Mezak & Pejic-Papak (Dlab et al, 2020).…”
Section: Discussionmentioning
confidence: 99%